Surface Characterization of Stainless Steel 316L Coated with Various Nanoparticle Types - Dhiaa J. Aldabagh; Thair L. Alzubaydi; Akram F. Alhuwaizi (International Journal of Biomaterials)
Background. Material tribology has widely expanded in scope and depth and is extended from the mechanical field to the biomedical field. The present study aimed to characterize the nanocoating of highly pure (99.9%) niobium (Nb), tantalum (Ta), and vanadium (V) deposited on 316L stainless steel (SS) substrates which considered the most widely used alloys in the manufacturing of SS orthodontic components. To date, the coating of SS orthodontic archwires with Nb, Ta, and V using a plasma sputtering method has never been reported. Nanodeposition was performed using a DC plasma sputtering system with three different sputtering times (1, 2, and 3 hours). Results. Structural and elemental analyses were conducted on the deposited coatings using XRD, FESEM, and EDS showing a unique phase of coating metals over their substrates with obvious homogeneous even deposition. A highly significant positive correlation was found between sputtering time and thickness of the achieved coatings. AFM revealed a reduction in the surface roughness of 316L SS substrates sputtered with all coating materials, significantly seen in V coatings. Conclusions. Sputtering time and coating material play a significant role in terms of microstructure and topography of the achieved coatings being the best in the Ta group; moreover, surface roughness was significantly improved by V coatings. Likewise, it is found to be sputtering time independent for all used coatings.